Challenges in postnatal care provision in Ethiopia - Bala, Elias Teferi; Roets, Lizeth (Frontiers in Public Health, 2022)
Background: Most maternal deaths occur during the first 48 hours after delivery, thus are critical for the monitoring of possible complications arising from the delivery. Quality postnatal care, can contribute to a decrease in maternal mortality and morbidity rates. Despite the importance of postnatal care, it is generally a very neglected aspect of maternal and child health services in most developing countries including Ethiopia. Objectives: The objective of the study was to describe the stance of postnatal care services as experienced by postnatal care providers and coordinators within the Ethiopian context Methods: A quantitative cross – sectional descriptive study was conducted to describe postnatal care services in Ethiopia. Data were gathered from 422 postnatal care providers and coordinators between 1 November and 30 November, 2018. A simple random sampling technique was used to select respondents. A self-administered questionnaire was used for data collection. The data were cleaned and coded and entered into Statistical Package for Social Sciences (SPSS) software program version 21 for analysis and the open-ended questions for qualitative enhancement were open coded and thematically analysed. Results: The findings revealed that that a lack of physical resources, infrastructure problems, cultural concerns, inadequate capacity building, inaccessibility of health services, unavailability of guidelines, lack of communication with healthcare users, and poor monitoring and evaluation were the identified as challenges that could influence the provision and utilisation of postnatal care services in Ethiopia. The respondents were of the opinion that the identified aspects must be addressed to improve postnatal care services. Conclusion: To improve postnatal care in Ethiopia the challenges experienced by postnatal care providers and coordinators have to be addressed to contribute to a reduction of maternal mortality and morbidity rates. A strategic action plan, with the active involvement of all stakeholders, must be developed to be implemented to address the challenges and improve postnatal care.